Analisis Kesantunan Berbahasa Dalam Film Pendek Negosiasi Kelas X Pada Saluran Youtube Cinta Bahasa - Endah Yustiani; Ninda Alifa; Widini Arti; Fairuzah Qolbi; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Kris Brantas Abiprayu (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The analysis of linguistic politeness in a short film about negotiations for class X on the Cinta Bahasa YouTube channel focuses on the analysis of politeness in negotiation activities. The purpose of analyzing linguistic politeness in the short film about class X negotiations is to find, describe, and evaluate the mistake in the dialogues in the videos titled "Short Film on Shop Rental Negotiations", "Land Sale and Purchase Negotiations", "Shop Sale and Purchase Negotiations", "House Sale and Purchase Negotiations", "Short Drama on Renting Rice Fields", "Video of Osim Meeting Negotiations", "Negotiations for the Preparation of the Indonesian Independence Day Ceremony" , and “Negotiation of Buying a Cell Phone". This research uses two research methods: a descriptive method with a qualitative approach and a theoretical method with a pragmatic approach. The data analyzed was collected using observation and note-taking techniques. The results of the data analysis are presented in the form of descriptions along with explanations for each linguistic politeness found in the videos. Ten maxims were found: the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement, the maxim of sympathy, the maxim of apology, the maxim of forgiveness, the maxim of emotion, the maxim of opinion, and the maxim of silence. This research provides an explanation of the use of linguistic politeness in the negotiation process. The language politeness that is most dominantly used on the Cinta Bahasa Youtube channel is compliance with the maxim of agreement and violation of the maxim of humilty. The benefit of this analysis is to provide an understanding of the appropriate use of language in accordance with language norms in the negotiation process, and readers can understand and use it in the context of good language as a result of this analysis.